2020
DOI: 10.1002/cae.22234
|View full text |Cite
|
Sign up to set email alerts
|

Research and application of situated teaching design for NC machining course based on virtual simulation technology

Abstract: As virtual simulation technology can display three‐dimensional materials as well as their dynamic cutting process and the learners’ motivation is enhanced in the situated learning environment, a virtual‐situated learning system for numerical control (NC) machining course is proposed to explore the learning effectiveness of learners when combining virtual simulation technology and the situation learning theory. This study aims to use the concept of embedding NC machining simulation system and the situated learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
0
13
0
2
Order By: Relevance
“…The traditional teaching method is difficult to ensure the participation of each student and the teaching quality of teachers, and the limitation of emergency experiment has a certain impact on students’ deep learning and understanding, so virtual simulation experiment is adopted to improve students’ learning effect and course satisfaction. Previous studies have also shown that virtual simulation experiment teaching has a positive impact on teacher teaching and student learning 34 , 35 . Therefore, it is of great significance to examine the effect of a virtual simulation platform.…”
Section: Introductionmentioning
confidence: 94%
“…The traditional teaching method is difficult to ensure the participation of each student and the teaching quality of teachers, and the limitation of emergency experiment has a certain impact on students’ deep learning and understanding, so virtual simulation experiment is adopted to improve students’ learning effect and course satisfaction. Previous studies have also shown that virtual simulation experiment teaching has a positive impact on teacher teaching and student learning 34 , 35 . Therefore, it is of great significance to examine the effect of a virtual simulation platform.…”
Section: Introductionmentioning
confidence: 94%
“…Finally, the optimal weights are obtained. The key of using genetic algorithm to solve the problem is to select the appropriate fitness function and genetic operation such as selection, crossover and mutation [33,34]. Among them, the structure of chromosomes is α, β, γ, δ rough empirical value is (0.2/0.25/0.35/0.2), the initial population is 40, and the value of each position of each chromosome fluctuates not more than 0.05, which is generated by random algorithm.…”
Section: Design Of Load Balancing Algorithm Based On Consistent H Ash and Genetic Algorithmmentioning
confidence: 99%
“…Moreover, it has been observed over the past few years that the student-centered virtual simulation learning environment allows the students for more active interpretation, analysis, evaluation, inference, explanation and self-regulation, and helps us to keep all the learners involved in the content. The resulting interactive learning module will also impose more responsibility on students for their own learning than the traditional lecture-based passive learning methodology [49,50]. This tends to create a cooperative learning atmosphere for students, so that in the process of sharing knowledge and experience, the students can enhance their thinking openness, self-confidence and systematic ability through assessment and self-regulation.…”
Section: B Strategy For the Integration Of The Proposed Teaching Metmentioning
confidence: 99%